« Y’a pas de “Djette” ici ! » : enjeux sociodiscursifs autour de la féminisation du terme DJ - Erica Lippert (Glad!)
The process of feminizing profession names, with the aim of banishing discrimination, is a major socio-political issue and a laborious linguistic policy in French. Based on the theoretical framework of discourse analysis, this article analyzes the various forms of feminization of the term DJ, including the form djette, and presents the results of a survey of women djs. The article focuses on both emotions and value judgments regarding the term djette. The results show that women artists align themselves behind a normative discourse based on folks linguistics, that they express the social and artistic discrimination of which they are victims, and that the term djette crystallizes these dynamics like a watchword.